Early vs Late Inguinal Hernia Repair in Preterm Infants - Franky, Franky; Handy, Handy (International Medical Journal Corp. Ltd, 2024)
Background: The topic of early versus late inguinal hernia repair in preterm infants has garnered significant attention in the medical literature, primarily due to the unique challenges posed by this vulnerable population. Literature Review: The literature surrounding early versus late inguinal hernia repair in preterm infants reveals a multifaceted landscape characterized by economic considerations, complication rates, and the timing of surgical interventions. The foundational study by Verhelst et al. (Verhelst et al., 2016) highlights the significant financial implications associated with emergency repairs, which incur higher direct medical costs compared to elective procedures. This study emphasizes that while clinical urgency may dictate the need for immediate intervention, the economic burden of such decisions cannot be overlooked, suggesting that elective surgeries could alleviate financial strain on healthcare systems while potentially improving patient outcomes. Conclusion: In conclusion, the reviewed literature collectively indicates that the decision-making process regarding inguinal hernia repair in preterm infants is complex and requires a nuanced approach. The interplay between economic considerations, complication rates, and surgical timing necessitates a careful evaluation of each case to optimize outcomes for this vulnerable population. Future research, particularly randomized controlled trials, is essential to establish clearer guidelines and best practices for managing inguinal hernias in preterm infants.